Protein hydrolysate as an efficient and environmental-friendly swelling inhibitor in clay formations - Yahya Dashti-Rahmatabadi; Hamid Saeidian; Javad Mokhtari; Zohreh Mirjafary (Journal of Petroleum Exploration and Production Technology)
Abstract Water-based drilling fluids, which are considered to be more environmentally friendly than their oil-based counterparts, are extensively used in the drilling operations. However, when these fluids are employed in clay formations, borehole stability becomes problematic due to the potential of clay swelling, unless appropriate inhibition strategies are implemented. This research aims to investigate the effect of a swelling clay inhibitor for use in water-based drilling fluids, making use of hydrolyzed protein composition (HPC) sourced from sheep’s wool waste. The HPC formulation consists of amino acids, peptides, and polypeptides with molecular weights ranging from 100 to 10,000 Dalton. The findings from various analytical methods suggest that amino acids, peptides, and polypeptides in the HPC interact with clay surfaces, rendering them hydrophobic and impeding swelling. The adsorption of the HPC onto bentonite (Bent) particles leads to a significant change in the zeta potential, shifting from − 32.5 to + 58.0 mV. Thermogravimetric analysis indicated that when temperatures surpass 200 °C, the Bent powder obtained from the aqueous solution of the HPC undergoes a notable increase in mass loss, quantified at 20.40%. The measured contact angle for the Bent-water interface was 27.57º. An increase in the contact angle to 36.45º on the surface treated with the Bent-inhibitor indicates the effectiveness of the inhibitor in decreasing wettability. The HPC exhibits a synergistic effect when it is combined with potassium chloride (KCl), a widely used clay swelling inhibitor. KCl operates via an osmotic mechanism, while the HPC acts through a capping mechanism. The comparison of rheological properties indicates that the fluid containing a 3.0 weight% (wt%) HPC solution demonstrates rheological characteristics that are almost indistinguishable from those of a 2.0 wt% KCl solution. The research indicates that the HPC is the preferable clay swelling inhibitor in montmorillonite-rich shales due to its inhibitory capabilities, cost efficiency, and eco-friendly nature. Graphical abstract